ANALYSIS OF MACROECONOMIC VARIABLES IMPACT ON STOCK MARKET PRICE IN INDONESIA STOCK EXCHANGE (IDX) FROM SECTOR2 PERIOD 2006-2016 - Melmambessy, Thiopillo .; Kindangen, Paulus .; Tumiwa, Johan . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Â ABSTRACT: One of the investment instruments available in this era is stock investment. Stock price movements can be closely linked to a country's macroeconomic conditions. There are many of research that has been conducted in terms of stock investment. However, investors are wiling to spend their funds in this type of investment, in order to attain greater return. This research aim to analyze the relationship between macroeconomic variables and stock market price from sector 2 in Indonesia Stock Exchange. This research is conducted to examine the simultan and partial influence between stock market price in and macroeconomic variables such as world oil price, interest rate, gross domestic product, sectoral stock price and money supply. Secondary data is the sources for this research, it will be based on quarterly data from January 2006 to December 2016. Time series regression is be the method that used to analyze the data.. The results reveal that the independent variables simultaneously influence stock market price, and by partially, the results confirm that money supply and sectoral stock price are significantly influence the stock market price.Keywords: Stock market price, world oil price, interest rate, gross domestic product, sectoral stock price, and money supply.